2021
DOI: 10.3390/su13158651
|View full text |Cite
|
Sign up to set email alerts
|

LED versus HPS Lighting: Effects on Water and Energy Consumption and Yield Quality in Lettuce Greenhouse Production

Abstract: High-pressure sodium (HPS) lighting is increasingly replaced by LED lighting in lettuce greenhouse cultivation. In contrast to HPS lighting, LEDs do not heat radiation. Therefore, the leaf temperature is significantly lower under LEDs. This raises the question of whether LED lighting has a positive impact on the reduction in water consumption during lettuce production. In this paper, we investigated this question and found that the water consumption of lettuce produced under LEDs was significantly lower (−15%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, LEDs do not emit as much heat as HPS lamps. This results in a comparable lower water consumption of crops produced under LEDs than HPS lamps [ 59 ] due to lower leaf temperature, and consequently transpiration rate [ 60 ]. However, it is worth noting, that the use of HPS lamps reduces costs during winter [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LEDs do not emit as much heat as HPS lamps. This results in a comparable lower water consumption of crops produced under LEDs than HPS lamps [ 59 ] due to lower leaf temperature, and consequently transpiration rate [ 60 ]. However, it is worth noting, that the use of HPS lamps reduces costs during winter [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Papers comparing lighting types also consistently found that LED lights (over fluorescent and metal halide, for example) provide many benefits, notably in their energy savings and easily manipulable lighting spectra [ 48 , 49 , 50 ]. LEDs also run at lower temperatures than previous lighting types, reducing heat waste, ensuring less water loss, and increasing the sustainability of the system [ 51 ]. Other factors were also investigated within studies, notably ensuring uniformity of lighting to guarantee unvarying growth within your system, which was highlighted as important, especially for VF systems with multiple stacked layers of growth [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%